2019
DOI: 10.1101/574020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enabling large-scale genome editing by reducing DNA nicking

Abstract: To extend the frontier of genome editing and enable the radical redesign of mammalian genomes, we developed a set of dead-Cas9 base editor (dBE) variants that allow editing at tens of thousands of loci per cell by overcoming the cell death associated with DNA double-strand breaks (DSBs) and single-strand breaks (SSBs). We used a set of gRNAs targeting repetitive elementsranging in target copy number from about 31 to 124,000 per cell. dBEs enabled survival after 5 large-scale base editing, allowing targeted mut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…It is possible that symbiotic interactions are widespread in eukaryotes but more difficult to capture because they are more challenging to identify and test experimentally, in part because of the large amounts of TEs that need to be manipulated simultaneously (e.g., retrotransposons in mammalian embryogenesis). The advent of genome editing and other largescale perturbations offers new powerful tools to overcome these challenges (Bourque et al 2018;Fuentes et al 2018;Smith et al 2019;Todd et al 2019). It is also possible that many mutualistic interactions are evolutionarily unstable and volatile because they are prone to tilt back and forth between disproportionately benefiting the TE (e.g., Drosophila telomeres) or the host to turn into full cooption events (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that symbiotic interactions are widespread in eukaryotes but more difficult to capture because they are more challenging to identify and test experimentally, in part because of the large amounts of TEs that need to be manipulated simultaneously (e.g., retrotransposons in mammalian embryogenesis). The advent of genome editing and other largescale perturbations offers new powerful tools to overcome these challenges (Bourque et al 2018;Fuentes et al 2018;Smith et al 2019;Todd et al 2019). It is also possible that many mutualistic interactions are evolutionarily unstable and volatile because they are prone to tilt back and forth between disproportionately benefiting the TE (e.g., Drosophila telomeres) or the host to turn into full cooption events (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased editing efficiency at each locus can be triggered by nuclease-induced double strand break. To avert the toxicity associated with double strand breaks, elegant 'Base editor' enzymes were engineered in which nuclease activity is replaced by base modification enzyme ( 11 ) , which can be used for simultaneous editing of over 13,000 ALU repetitive elements in human cells using a small number of guides ( 12 ) . Other Cas9-based tools include repressors, activators and targeted insertion of DNA.…”
Section: Genome Editingmentioning
confidence: 99%
“…We previously designed repetitive sgRNAs to target about 26000 human LINE-1 (sgRNA-LINE-1) and about 161000 Alu (sgRNA-Alu) elements 14 based on their consensus sequences to generate numerous double-strand DNA breaks and initiate apoptosis (or otherwise render the cell non-viable). These lethal sgRNAs may be expressed in a cell prophylactically, being benign to the cell until it encounters the Cas9 nuclease ( Fig.…”
Section: Design and Identification Of Lethal Sgrnas Targeting Transpomentioning
confidence: 99%
“…While attempting large-scale genome editing at these transposable elements, we have previously shown that targeting LINE-1 sequences in the genome using the original CRISPR-Cas9 system in HEK 293T, did not yield the survival of any edited clones 14 . Our hypothesis was that Cas9 would trigger a massive number of DSBs at these targets, overwhelming the cell's ability to repair this damage.…”
Section: Introductionmentioning
confidence: 99%